2020
DOI: 10.3390/cancers12040843
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Tissue Specific miRNA Expression Pattern and Functional Analysis Associated to Colorectal Cancer Patients

Abstract: An increasing number of studies suggest the implication of microRNAs (miRNAs) in colorectal (CRC) carcinogenesis and disease progression. Nevertheless, the basic mechanism is not yet clear. We determined plasma miRNA expression levels using Agilent microarray technology followed by overlapping with The Cancer Genome Atlas (TCGA) tissue data and a qRT-PCR validation step and analysis of the altered miRNA signatures to emphasize new mechanistic insights. For TGCA dataset, we identified 156 altered miRNAs (79 dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 42 publications
1
31
1
Order By: Relevance
“…The isoform expressions of the DEmiRNAs were identified using the R package miRNAmeConverter . The common consistently and differentially expressed (Co-DE) miRNAs were obtained using intersected analyses comparing TCGA and microarray datasets ( Cojocneanu et al, 2020 ). The targeted mRNAs of the Co-DEmiRNAs were predicted using three online analytical software tools including miRDB 2 , TargetScanHuman (version 7.2) 3 , and miRWalk ( Agarwal et al, 2015 ; Dweep and Gretz, 2015 ; Chen and Wang, 2020 ) 4 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The isoform expressions of the DEmiRNAs were identified using the R package miRNAmeConverter . The common consistently and differentially expressed (Co-DE) miRNAs were obtained using intersected analyses comparing TCGA and microarray datasets ( Cojocneanu et al, 2020 ). The targeted mRNAs of the Co-DEmiRNAs were predicted using three online analytical software tools including miRDB 2 , TargetScanHuman (version 7.2) 3 , and miRWalk ( Agarwal et al, 2015 ; Dweep and Gretz, 2015 ; Chen and Wang, 2020 ) 4 .…”
Section: Methodsmentioning
confidence: 99%
“…et al, 2019 ; Wu S.G. et al, 2019 ; Condrat et al, 2020 ). miRNAs could be readily detected in circulation and carry information regarding the origin of a neoplasm, thus serving as diagnostic and prognostic biomarkers in the development of tumors ( Hummel et al, 2010 ; Blondal et al, 2013 ; Qi et al, 2013 ; Zhang et al, 2016 ; Liu et al, 2017 ; Świtlik et al, 2019 ; Cojocneanu et al, 2020 ; Wang et al, 2020 ). An increasing number of studies have reported various expression levels of miRNAs in LUAD ( Cazzoli et al, 2013 ; Zhong et al, 2018 ), although findings remain inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that miRNAs can be identified in a variety of body fluids, including plasma, saliva, urine, seminal fluids, breast milk, cerebrospinal fluid and more recently also in feces, leading to the definition of circulating miRNAs [70][71][72][73][74]. Every miRNA has a unique nucleotide sequence and expression pattern in a certain cell type; however, although miRNAs show a high tissue specificity, body fluids can contain different or unique circulating miRNAs, that can putatively have several hundred gene targets, thereby generating an intricate picture [75]. Circulating miRNAs have been found associated with EVs, with high-density lipoproteins or with proteins involved in their processing such as the argonaute protein.…”
Section: Circulating Mirnasmentioning
confidence: 99%
“…Therefore, patient care management remains an important clinical challenge due to the lack of availability of prognostic markers that could stratify a patient’s risk. In the past few years, there has been an increased interest in verifying the clinical utility of coding and noncoding genes as important biomarkers for prognostic, diagnostic, and therapeutic targets [ 2 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%